2006
DOI: 10.1007/s10531-004-2178-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Dalbergia monticola (Fabaceae) an Endangered Tree Species in the Fragmented Oriental Forest of Madagascar

Abstract: There is an urgent need to maintain and restore a broad genetic base for the management of Dalbergia monticola, a very economically important but endangered tree species in Madagascar. Random amplified polymorphism DNAs (RAPDs) and chloroplast microsatellite markers were used to quantify the genetic variation and to analyse the geographic distribution of diversity. Ten locations covering most of the natural range were sampled. Sixty-three RAPD polymorphic and 15 monomorphic loci were obtained from 122 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Furthermore, fig domestication in all the Mediterranean regions has been influenced by human activities [44] [50]. Thus, the fragmentation of tree resources can significantly increase this type of activity [51]. In the current research, a weak genetic structure was observed probably due to the circulating these genotypes.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, fig domestication in all the Mediterranean regions has been influenced by human activities [44] [50]. Thus, the fragmentation of tree resources can significantly increase this type of activity [51]. In the current research, a weak genetic structure was observed probably due to the circulating these genotypes.…”
Section: Discussionmentioning
confidence: 48%
“…The LGM period was also associated with rainfall variations in equatorial East Africa, but the peak glacial drought overlapped only partly with the LGM proper (Gasse et al ., ; Verschuren et al ., ). At a local scale, paleo‐records from Mauritius and Madagascar also supported drier conditions during the LGM (Gasse & Van Campo, ; Andrianoelina et al ., ; Van Der Plas et al ., ). However, the results from demographic inference in C. mauritiana did not reveal an impact of the wet/dry spells that alternated during the Holocene in SWIO and East Africa (Gasse & Van Campo, ; Gasse et al ., ; Verschuren et al ., ), suggesting that climate changes in the Holocene period differentially impacted Reunion Island forest compared with the climatic changes of the LGM.…”
Section: Discussionmentioning
confidence: 99%
“…In S. insulare , very low values, smaller than H e = 0.25, have been estimated for some islands, but this parameter is high for others (Tahuata, Moorea), and does not show a specific pattern compared with other tree species such as Vitellaria paradoxa or Dalbergia monticola exhibiting similar values at the sub‐population level (Fontaine et al. , 2004; Andrianoelina et al. , 2005).…”
Section: Discussionmentioning
confidence: 94%